(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2024)
Determination of stature from head length is equally significant like determining from other body parts. A cross sectional study on estimation of stature from head length was conducted in the population of Hyderabad, Telangana at Malla reddy institute of medical sciences. Study population consists of 154 members, who include 75 males and 79 females, participants were in the age group of 18-23 years. Data was collected from participants after obtaining informed consent. Measurement of head length was taken from the top of vertex to the bottom of the chin in centimeter (cm) scale. A linear regression formula was obtained to correlate head length and height. Linear regression equations for total study population is Y=77.59 + 4.135( HL), male population is Y=118.5 + 2.46 (HL) and female population is Y=159.71 + 0.062 (HL). Statistical results of the study, R2 = 0.333, Standard error = 0.475 and P value <0.0001 reveals statistical significance of the study. Separate formulae for male and female individuals will give more accurate results. ±5 cm difference in the stature was observed in the study population with the derived equation. Height is aproximately 8 times the head length in Female population and 7.5 times in male population in the study group.